PELATIHAN PROGRESSIVE MUSCLE RELAXATION (PMR) UNTUK MENINGKATKAN KUALITAS TIDUR PENDERITA HIPERTENSI DI MENGANTI KABUPATEN CILACAP - Kasron, Kasron; Susilawati, Susilawati; Subroto, Wishnu (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Hypertension (HT) is a major risk factor for cardiovascular disease which is the leading cause of death in the world. HT is in the first rank as the most common disease due to lifestyle changes. Patients with HT may experience several signs and symptoms such as changes in the retina, headaches, dizziness, and difficulty breathing. HT can cause sleep dissorder. Poor sleep quality can have an effect on decreasing people's productivity. This community service was carried out in RW 10 in Menganti Village, where information was obtained that there were still many residents who did not know specific information about sleep quality and its management using the Progressive Muscle Relaxation (PMR) method. The service method is carried out by training, demonstrations about PMR. In this service, demonstrations about PMR were successfully carried out. The results obtained were that cadres and residents were able to know about sleep quality and were able to demonstrate PMR intervention. After this service was carried out, residents with sleep disorders began to be moved by the importance of sleep quality.